91.5k views
2 votes
What does g equal if
-g - 9 = -10g

2 Answers

6 votes

Answer:

1

Explanation:

I like to rearrange my equations by putting the larger variable on the left. It doesn't change anything.

-10g =-g-9

First we need to move the -1g over with the -10g by adding it. You add it because it was a negative.

So -10g+1g= -9

Now combine and you get -9g=-9

Divide both sides by -9 to get g by itself.

G =1

User Bridge
by
5.1k points
5 votes

Answer:

19

Explanation:

19 because 19-9=10g

User Micromegas
by
4.7k points